Sustainable Practices in Learning Factories: Technology for SDG4: Penerapan Teknologi Berkelanjutan dalam Learning Factories untuk Mendukung SDG 4 - Sunarya, Po Abas; Friandi, Sendy Zul; Santoso, Nuke Puji Lestari; Abbas, Maulana; Xolani, Zanele (Technomedia Journal, 2025)
Learning factories serve as innovative platforms to promote sustainable education by integrating advanced technologies, contributing directly to achieving Sustainable Development Goal 4 (SDG4), which focuses on ensuring inclusive and equitable quality education and lifelong learning opportunities for all. This study investigates the application of sustainable practices in learning factories, aiming to identify technological innovations that enhance education while promoting resource efficiency and accessibility. The objective of this research is to explore how these technologies can address educational challenges and contribute to sustainable development. Employing a mixed-methods approach, this research combines in-depth qualitative case studies of learning factories with quantitative data from surveys and interviews conducted with educators, students, and industry stakeholders. The findingsreveal that implementing technologies such as automation, virtual and augmented reality, and digital twins improves learning outcomes by providing immersive, hands-on experiences while minimizing environmental impacts. Additionally, the results highlight the importance of fostering partnerships between academic institutions and industries to create a collaborative ecosystem for sustainable innovation. The conclusion emphasizes the transformative role of learning factories in advancing sustainable education through technology, suggesting that broader adoption of these practices can accelerate progress toward SDG4. This study offers practical recommendations for educators, policymakers, and industry leaders to integrate technology-driven sustainability in educational environments, thus supporting global efforts toward equitable and quality education.